2016
DOI: 10.1089/scd.2015.0049
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelial Progenitor Cells in Maintaining Stemness and Enhancing Differentiation of Mesenchymal Stem Cells by Indirect Cell–Cell Interaction

Abstract: A hot issue in current research regarding stem cells for regenerative medicine is the retainment of the stemness and multipotency of stem cell. Endothelial progenitor cells (EPCs) are characterized by an angiogenic switch that induces angiogenesis and further ameliorates the local microenvironment in ischemic organs. This study investigated whether EPCs could modulate the multipotent and differential abilities of mesenchymal stem cells (MSCs) in vitro and in vivo. We established an EPC/MSC indirect Transwell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…We could prove that the proliferation rate of MSCs was highly stimulated by paracrine-acting soluble mediators secreted from T17b EPCs. These results conform with other studies demonstrating that CM from endothelial cells or EPCs enhanced the proliferation of MSCs [Villars et al, 2000;Wen et al, 2016]. Conversely, CM from MSCs had no effect on T17b EPC proliferation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We could prove that the proliferation rate of MSCs was highly stimulated by paracrine-acting soluble mediators secreted from T17b EPCs. These results conform with other studies demonstrating that CM from endothelial cells or EPCs enhanced the proliferation of MSCs [Villars et al, 2000;Wen et al, 2016]. Conversely, CM from MSCs had no effect on T17b EPC proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…A BrdUrd ELISA was performed to investigate the effect of coculturing MSCs and T17b EPCs on cell proliferation. Our results display a strong effect of T17b EPCs on MSCs proliferation, which is coherent with previous studies demonstrating that endothelial cells as well as EPCs have an impact on MSC proliferation [Steiner et al, 2012;Wen et al, 2016]. This effect seems to be stimulated by heterotypic cell-cell contacts as well as paracrine-acting mediators if CM was used.…”
Section: Discussionsupporting
confidence: 92%
“…However, the commonly used “endothelial-specific” transgenic Cre lines used to track the EC lineage also express within myeloid lineage – cells can adopt the EC fate 50 and contribute to arterial calcification in T2D 51, 52 . Moreover, co-culture of endothelial progenitors with mesenchymal progenitors have pointed to paracrine interactions between multipotent Sox2-positive populations in both lineages that promote osteogenic mineralization 53 . Thus, a mechanistically more important consequence of EC de-differentiation during the EndMT likely relates to alterations in paracrine endothelial –mesenchymal signals that program an osteogenic fate of adjacent VSM and mesenchymal progenitors.…”
Section: Rodent Models Of Arterial Calcification In Type I Diabetesmentioning
confidence: 99%
“…Even though many previous studies utilized a single type of cells for transplantation, however, some studies have suggested that coculture or transplantation of more than one type of cells may improve the biological properties of stem cells . It has been demonstrated that coculture of human umbilical vein endothelial cells and MSCs can form a vascular tissue‐like network in vitro through the induction of VEGF production .…”
mentioning
confidence: 99%